A prospective observational study on management approaches for non-healing ulcers in dermatology: From conventional to advanced modalities. - Dr. Poonam Tapsale; Kadam, Dr. Vishal; Dr. Onkar Lande; Dr. Madan S. Hardikar; Dr. Nitin Chaudhari (Student's Journal of Health Research Africa, 2025)
Background: Non-healing ulcers are a major dermatological challenge, leading to prolonged morbidity, infection, and impaired quality of life. Conventional care often fails to achieve complete healing, prompting the need for advanced modalities such as Negative Pressure Wound Therapy (NPWT), Platelet-Rich Fibrin (PRF), growth factors, and skin substitutes. Methods: A prospective observational study was conducted at a tertiary care hospital from February 2024 to February 2025, enrolling 105 patients with ulcers persisting beyond six weeks. Participants were randomized into three groups (n=35 each): (i) Conventional care (saline dressings, antibiotics, compression/off-loading), (ii) Advanced A (NPWT with topical growth factor), and (iii) Advanced B (PRF with bioengineered skin substitute). Baseline evaluation included demographics, comorbidities, ulcer type, size, and duration. Patients were followed weekly for 12 weeks. The primary outcome was the percentage reduction in ulcer area; secondary outcomes included time to granulation, complete healing rate, and infection control. Data were analyzed using SPSS v26.0 with ANOVA and Chi-square tests, considering p<0.05 as significant. Results: Baseline characteristics were comparable across groups (p>0.05). At 12 weeks, mean ulcer area reduction was 40% in the Conventional group, 80% in Advanced A, and 78% in Advanced B (p<0.001). Mean time to granulation was significantly shorter with advanced modalities (12.5 ± 4.8 days in Advanced A; 13.1 ± 5.2 days in Advanced B) versus Conventional care (24.2 ± 6.1 days). Complete healing occurred in 75%, 90%, and 87.5% of patients, respectively. Conclusion: Advanced wound therapies, particularly NPWT with growth factors and PRF with skin substitutes, markedly accelerate granulation, enhance ulcer area reduction, and improve healing outcomes compared to conventional care. Recommendations: Incorporation of advanced modalities into standard dermatological wound management is advised, with future multicentric trials warranted to evaluate cost-effectiveness and establish standardized treatment protocols.